Petroleum Pump Price Swing and Consumer Price Index Nexus in Nigeria: New Evidence From NARDL - Sakanko, Musa Abdullahi; Adejor, Gabriel Attah; Adeniji, Sesan Oluseyi (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
The study analyses the role of the petroleum pump price on the consumer price index in Nigeria, using the Nonlinear Autoregressive distributive lag method was used to estimate the time-series data, spanning from 1980 to 2020. The study reveals a long-run equilibrium was found between the consumer price index and petroleum pump price measures. The empirical results obtained revealed an asymmetric relationship between the petroleum pump price and the consumer price index in Nigeria. The study recommended that the policymakers should transparently commit resources into rehabilitation and maintenance of domestic refineries to enhance their functionality and as well reduce importation cost to curtail frequent petroleum pump price adjustment that spiral domestic inflation.